New records of phytoplankton for Bangladesh. 7. Phacus spp. - Khondker, Moniruzzaman; Bhuiyan, Rauf Ahmed; Yeasmin, Jenat; Alam, Munirul; Sack, R Bradley; Huq, Anwar; Colwell, Rita R (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Thirteen species of Phacus hitherto not reported from Bangladesh have been described and illustrated. Freshwater ponds at southern districts of Pirojpur and Barisal revealed these presence of the species. Â Key words: Phytoplankton, New records, Bangladesh, Phacus, Ponds doi:10.3329/bjb.v37i1.1564 Bangladesh J. Bot. 37(1): 55-60, 2008 (June)